A comparison of body segment inertial parameter estimation methods and joint moment and power calculations during a drop vertical jump in collegiate female soccer players - Arena, S. L.; McLaughlin, K.; Nguyen, A.-D.; Smoliga, J. M.; Ford, K. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Athletic individuals may differ in body segment inertial parameter (BSIP) estimates due to differences in body composition, and this may influence calculation of joint kinetics. The purposes of this study were to (1) compare BSIPs predicted by the method introduced by de Leva1 with DXA-derived BSIPs in collegiate female soccer players, and (2) examine the effects of these BSIP estimation methods on joint moment and power calculations during a drop vertical jump (DVJ). Twenty female NCAA Division I soccer players were recruited. BSIPs of the shank and thigh (mass, COM location, and radius of gyration) were determined using de Leva`s method and analysis of whole-body DXA scans. These estimates were used to determine peak knee joint moments and power during the DVJ. Compared with DXA, de Leva`s method located the COM more distally in the shank (P = .008) and more proximally in the thigh (P < .001), and the radius of gyration of the thigh to be further from the thigh COM (P < .001). All knee joint moment and power measures were similar between methods. These findings suggest that BSIP estimation may vary between methods, but the impact on joint moment calculations during a dynamic task is negligible.